Klimawandel, Sicherheit und Migration in Wissenschaft und Politik – Gutachten im Zwielicht - Bendel, Petra; Haase, Marianne (Gesellschaft, Wirtschaft, Politik, 2010)

Land unter? (Menschen-)Rechtliche Konsequenzen des Klimawandels für Migrantinnen und Migranten - Bendel, Petra; Haase, Marianne (Zeitschrift für Menschenrechte, 2010)
Keywords: Klimawandel; Migration; Menschenrechte

The Europeanization of Control: Venues and Outcomes of EU Justice and Home Affairs Cooperation - Bendel, Petra; Ette, Andreas; Parkes, Roderick; Haase, Marianne (Lit, 2011)
The transfer of sovereignty from the member states to the European Union in decisions about migration and asylum, justice and order has been one of the most surprising task expansions in the European project. This book sheds light on these extraordinarily dynamic institutional developments and the resulting policy outcomes. Comprising both conceptual and empirical contributions, the volume asks whether established theoretical schools of thought still hold true or whether the institutional conditions induced by the Lisbon Treaty have led to new modes of interaction and given weight to rival explanations.
Keywords: Europäische Union; Justiz- und Innenpolitik